Study of the quality assurance in cardiac Department services - S. MANIKANDAN, (International Journal of Pharma and Bio Sciences, 2017)
The aim of this study was to develop a graphical method of risk-stratified outcome To study the scope of the Cathlab & Cardiothoracic Operation theater. To study and asses the Quality Assurance Programmed with indicators in hospitals. To recommend measures to improve the quality in case non-compliance and partial compliance is found in some parameters. To provide multi-specialty and super specialty health care services undergone roof. To provide health care based on modern technology and expertise at a cost-ensuring valve for money. To provide a delightful ambience and excellent medical care with a human touch by integrated teamwork and quality systems with monitoring and feedback. To carry out continuous up gradation of technology and human resource development activities in a congenial and safe environment. To be an environment friendly and ecologically conscious organization Cardiac disease diagnostics and treatment services are commensurate to the services provided by hospital. To recommend measures to improve the quality in case non-compliance and partial compliance is found in some parameters. To recommend measures to improve the quality in case non-compliance and partial compliance is found in some parameters.